The Correlation of The Ability to Memorize the Al-Quran with The results of Learning Physics - Nurul Husna; Tarmizi Tarmizi; Susanna Susanna (Asian Journal of Science Education, 2019)
The Correlational research with this quantitative approach aims to determine the relationship between the ability to memorize the Al-Quran and the results of physics learning at the Ulumul Quran Senior High School Sigli. The sample in this study were students of Ulumul Quran State Senior High School class XI Sigli totaling 29 people. Data collection was obtained with documentation for the ability to memorize the Al-Quran and test instruments for the results of learning physics. Processing data using correlation coefficients and hypothesis testing through the product moment equation. The results of the correlation coefficient show the ability to memorize the Al-Quran with the results of physics learning students of Ulumul Quran Public High School Sigli with a calculation of 0.427 categorized as medium and the results of hypothesis testing obtained rcount rtabel that is 0.427 0.367 then the research hypothesis is rejected, meaning there is a significant relationship between the ability to memorize the Al-Quran and the results of physics learning of the students of the Ulumul Quran State High School Sigli.